PROBLEMS OF MEDICAL EDUCATION OF FOREIGN CITIZENS IN MEDICAL UNIVERSITY - Smirnov, S.M.; Pobedyonna, G.P.; Lavrinchuk, I.A.; Shooper, V.A.; Matyukhin, P.V. (World of Medicine and Biology, 2013)
The problems of medical education of foreign citizens in SE “Lugansk state medical university” are considered at the article, were detected the ways of their solving.
Keywords: medical education; foreign students; problems